The Association Between Internet Addiction and Social Anxiety Among Adolescents: A cross sectional study from Dharan - Mishar, Sanjeev Kumar; Pandey, Sandip; Kunwar, Binita (Journal of Psychiatrists' Association of Nepal, 2022)
Introduction: Internet addiction is an increasingly prevalent phenomenon affecting both social and psychological aspects of an individual. Internet addiction is thought to be the result of cognitive distortions such as those seen in social anxiety. In light of this theory, this study is an attempt to see if there is an association between internet addiction and social anxiety. Methodology: A cross sectional study was conducted among students from class 10-12 of a school in Dharan using convenient sampling method. The students were evaluated using the Young Internet Addiction Test (IAT) and the SPIN Inventory. Descriptive data was analysed using number and percentage. Association between IAT and SPIN was assessed using chi square test. Correlation between the IAT and SPIN scores was assessed using Pearson correlation. Result: Of the 245 students, 52.7% were female and 38.4% were from class 10. 44.9% students had mild internet addiction 29.4% had moderate and 0.4% had severe level of internet addiction. 57.4% students had both internet addiction and social anxiety (p < 0.01). There was a small positive correlation between IAT and SPIN scores (r value 0.3, p value < 0.01). Conclusion: Internet addiction and social anxiety are significantly associated with each other. Further studies need to be carried out to establish the cause-effect relationship.